2006
DOI: 10.1079/phn2005911
|View full text |Cite
|
Sign up to set email alerts
|

Impact of promotion of mango and liver as sources of vitamin A for young children: a pilot study in Burkina Faso

Abstract: Objective: To assess the effectiveness of a behaviour change approach, with or without financial support, in improving vitamin A (VA) intake and serum retinol concentration through mango and liver consumption by children. Design: A parallel design (no control area) was used to assess changes in VA intake and serum retinol over a 15-week period. Setting and subjects: A pilot study was implemented in the Department of Kokologho, a rural area in central west Burkina Faso. One hundred and fifty children aged 2-3 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
4
13
0
Order By: Relevance
“…These results corroborates previous studies [2,23]. It could probably be explained by the duration of the intervention and the poorly controlled feeding of children in both groups.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results corroborates previous studies [2,23]. It could probably be explained by the duration of the intervention and the poorly controlled feeding of children in both groups.…”
Section: Discussionsupporting
confidence: 93%
“…There were very high levels of VA deficiency among preschool children up to 56.8% and 53.8% in control Group and treatment group respectively, which is a major public health concern. VA inadequacy levels much higher than the 36.2% low serum concentration reported by Nana in preschool children in rural Burkina Faso [23].…”
Section: Discussionmentioning
confidence: 57%
“…For example, Nana, Brouwer, Zagré, Kok, and Traoré (2006) found that promotion of mango and liver consumption increased VA intakes and serum retinol levels among children in Burkina Faso and Low et al (2007) found that promoting orange sweet potatoes had similar effects in Mozambique. This work moves beyond the traditionally examined outcomes of intake, nutritional status, and growth to examine whether diet-based interventions have the potential to improve child health as measured by morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…In Burkina Faso, malnutrition and micronutrients deficiencies are two of the biggest constraints to achieve the millennium development goals. These two problems are widespread and constitute a serious public health problem [3]. Diets rich in fruits and vegetables, which bring good micronutrients and phytochimic compound for health, can be beneficial in the fight against malnutrition and obesity [4].…”
Section: Introductionmentioning
confidence: 99%